Penguatan Daya Saing Komoditas Kelapa Sulawesi Utara dalam Pasar Asia Pasifik melalui Unit Bisnis Strategis Pengeloaan Kelapa Terpadu Skala Industri Pedesaan - Jimmy Reagen Robot; Nancy Tuturoong (Universitas Bumigora, 2023)
This study is a strategic analysis of the current condition of empowering the coconut industry in North Sulawesi which is reflected in the performance of national exports. The hypothesis that has been developed refers to the comparative strength of the competitiveness of countries in the Southeast Asian region in facing the Asia Pacific free trade era as a turbolence effect of world free trade openness which has caused international market competition to become increasingly extreme due to the rapid advancement of information technology. Vibration of the rural economy has significance for the resilience of a country's national economy. On the other hand, open access to world information that has reached rural areas is not fragmented by the touch of technological advances in the coconut processing industry in rural areas and is still trapped by its traditional stigma. The analysis of this paper elaborates on the implementation of value engineering innovations in downstream integrated coconut processing on a rural industrial scale as a breakthrough in efforts to accelerate the distribution of skills and welfare of rural farming communities in improving the final quality of downstreaming people's coconut products, as a contribution to bridging the reality of inequality in economic empowerment and applied technology in rural North Sulawesi.